A CHRISTIAN READING OF THE BUDDHIST VIEW OF LIFE IN THE LIGHT OF VATICAN II - Kochumuttom, Thomas (Journal of Dharma, 2008)
Vatican Council II, in its historic document on the religions of the world, Nostra Aetate, has made a very positive statement on Buddhism. It reads as follows: “Buddhism in its multiple forms acknowledges the radical insufficiency of this shifting world. It teaches a path by which, men in a devout and confident spirit, can either reach a state of absolute freedom or attain supreme enlightenment by their own efforts or by higher assistance.”1 This brief statement, indeed, reflects the new outlook that the Catholic Church wants to be adopted in her ongoing interaction with other religions. This essay makes an attempt to spell out its details and the enriching elements of Buddhism from a Christian perspective.